The structure of verdal word-building units: morphonological aspect (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
Morphonological structure of deverbatives of the third morphonological type in modern Ukrainian language is considered in the article. The morphonological models are installed, probable morphonological changes are predicted.
Keywords: word-building morphonology; deverbatives; word-building unit; morphonological types; morfonological classes